Ostatni gliniany dom z Chorek w powiecie łęczyckim i jego mieszkańcy - Czepas, Piotr (Zeszyty Wiejskie, 2015)
The present article focuses on the history of the farmers’ cottage in the Chorki village, Łęczyca poviat. It was built of straw and clay in the late 19th century. Until 2007, it was inhabited by the Skalski family. The house was documented for the first time in the 1960s by Bożenna Paszkowska-Wróblewska, an ethnographer from the Museum of Archaeology and Ethnography in Łódź, as part of the studies of clay buildings of the Chorki village. At present, it is the last At present, it is the last surviving example of a clay house in this village. Abandoned, it is meant to be demolished soon.